Modeling Transit Flow Through Port Gates and Connecting Channel in Baltic Sea—Liepaja Port—Liepaja Lake System - Frishfelds, Vilnis; Sennikovs, Juris; Bethers, Uldis; Murawski, Jens; Timuhins, Andrejs (Frontiers in Marine Science, 2021)
This study investigates a water transport features by extending Copernicus Marine Environment Service (CMEMS) to the Liepaja coast-port-channel-lake system with a two-way nested model. The Liepaja lake and Liepaja port are connected by Trade channel. The Liepaja port has three gates - the openings in wave breakers connecting the port aquatory with the Baltic sea. Each of gates has a corresponding dredged channel for securing the navigation. A hydrodynamic model is set up to study the flow and water level in this system. The area of the port gates, port and Trade channel are resolved by 33 m grid. The model results are verified against currents and sea level observations inside/outside port, Trade channel and Liepaja lake. Results and observations show that strong currents occur in the Trade channel in case of rapid sea level change in Baltic sea despite the Trade channel is rather shallow at the connection with Liepaja lake. The northern part of the Liepaja lake gets filled with brackish water during storm surge events. The channel has notable alternating current also during a relatively calm weather due to the port seiches. Long and narrow shape of the channel implies the Helmholtz type oscillations between the lake and the port with a period in approximately semidiurnal range. Hydrodynamic simulations describe well these oscillations but the phase of hourly scale oscillations in the port may differ in case of weak external forcing. Water exchange is significantly increased by the transit (gate to gate) sea currents. This transit flow usually occurs between South or Central gate and the North gate carrying sea water into the port. Northward flow of the surface layer is more characteristic in the port aquatory due the prevailing south-western winds. There are intense morphological processes at the coastline and underwater slope near the Liepaja port due to a sandy western coastline of Latvia, long fetch of the waves and strong currents at the port gates. Liepaja port is one of the Latvian ports in HywasPort operational service of hydrodynamics, waves and siltation.